Influence of soft block crystallization on microstructural variation of double crystalline poly(ether‐mb‐amide) multiblock copolymers. Issue 3 (26th October 2018) - Cao, Yiyu; Zhu, Ping; Wang, Zefan; Zhou, Yong; Chen, Haiming; Müller, Alejandro J.; Wang, Dujin; Dong, Xia
Abstract: This work reports the crystallization behavior of a series of poly(ether‐ mb ‐amide) multiblock copolymer (PEAc) samples, composed of long‐chain carbon polyamide 1012 (PA1012) as hard segments and poly(tetramethylene oxide) (PTMO) as soft segments. Rheological and dynamic mechanical results showed that PA1012‐ mb ‐PTMO multiblock copolymers are microphase segregated in the both melt and solid states, forming two partially miscible phases with distinct crystallization and glass‐transition temperatures that depend on composition. The copolymers are probably in the weak segregation limit, as the PA1012‐rich phase can break out and form spherulitic templates during cooling from the melt. For the PA1012‐ mb ‐PTMO copolymers with long PTMO segments, it was found that the crystallization of the PTMO‐rich phase induced a variation in the long period as temperature decreased. This effect was related to the content of PTMO segments. At room temperature, only the PA1012‐rich phase crystallized, whereas PTM‐ rich phase remained amorphous within the interlamellar regions of the PA1012 spherulitic templates. Upon further cooling, the PTMO‐rich phase crystallized forming crystalline lamellae located in between the adjacent PA1012 lamellae, forming double crystalline spherulites. Based on the research results, a schematic model was proposed to describe the multistage crystallization behavior of PA1012‐ mb ‐PTMO copolymers. Abstract : This work examines the crystallization behavior of PA1012‐ mb ‐PTMO copolymers. At 40°C, the interlamellar spacing is filled with amorphous (PTMO)‐rich phase. When the temperature drops to −40°C, the reasons for the reduction in the long period L are contraction of the amorphous phase and crystallization of PTMO‐rich phases, and the crystallization of PTMO‐rich phase takes a dominant role. Under −40°C, the PTMO lamellae are formed within the interlamellar region of PA1012‐rich phase, and the amount of intercalated structure shows a dependence on the weight content of PTMO.